Epidemiological Trends and Clinical Characteristics of Childhood Leukemia in Saudi Arabia: A Review - Owaidhah, Nadyah A; Khawaji, Zakaria Y; Alahmadi, Mohammed A; Badawi, Ahmad S; Mogharbel, Ghazi H; Makhdoom, Osama N (Curēus (Palo Alto, CA), 2022)
Leukemia is the most prevalent type of cancer among children in Saudi Arabia. It has variable clinical presentations and accounts for a large scale of mortality and morbidity. Acute lymphoblastic leukemia (ALL) constituted the majority of pediatric leukemic cases with male gender predisposition. The most common first presentation that patients come with are manifestations of anemia, thrombocytopenia, and fever. Bone pain, fatigue, weight loss, organomegaly, and pale skin are among the commonest manifestations of pediatric leukemia. Childhood ALL and acute myeloid leukemia (AML) clinical manifestations seem to be very similar, even though there’re some considerable differences in how common the clinical characteristics are. Chromosomal abnormalities are taken into consideration to determine survival and treatment. PubMed and Google Scholar were searched for the childhood leukemia population in Saudi Arabia. Our review article aims at providing comprehensible and updated statistical data on the different types of leukemia and their clinical presentations in Saudi Arabia.